Futebol e a construção da imagem de treinadores pela mídia: um estudo a partir das notícias de um site de grande visitação na web - Silva, Roberto Nascimento Braga da [UNESP] (2014)
The relationship between sport and media is inseparable today. Therefore, this study aimed to quantify the number of news reports about male professional soccer, and analyze the construction of the image associated with soccer coaches. To this end, every sports news from a largely accessed website was collected for 30 days. It was concluded that, in Brazil, these news are directed to male professional soccer and its coaches, with the ideas concerning the latter being mainly related to their competence and the tactical/technical articulation of the team.